Challenges Arising from Self-Administered Misoprostol for Unintended Pregnancies Amidst Covid-19 Lockdown - Zubaida Masood; Rahila Imtiaz; Fauzia Ali; Samia Husain; Mataa-; Jarry masood (ziauddin University, 2024)
Background: The COVID-19 pandemic placed unprecedented strain on healthcare globally, which exacerbated factors leading to unplanned pregnancies. This study aimed to assess the complications of self-administration of misoprostol for miscarriage during the COVID-19 lockdown. Methods: This was a retrospective cohort study conducted at the Department of Obstetrics and Gynecology, Abbasi Shaheed Hospital, Karachi, from 1st March to 30th September 2020. Case records were compiled and analyzed. All women who reported after self-administration of misoprostol were included. The primary outcome measure was complications; anemia, blood transfusion, heavy bleeding, shock, sepsis, ruptured ectopic pregnancy, and ruptured uterus. A bivariable analysis was done to see the effect of gestational age at intake of misoprostol on the complications encountered, the chi-square test or Fischer's exact test was also applied. Results: In this study, a total of 54 cases were studied. The most common complication was anemia (63%) followed by incomplete abortion (61.1%). Heavy bleeding (p˂0.001), blood transfusion (p=0.020), and incomplete abortion were significantly (p˂0.001) more common in women who used misoprostol at gestational ages greater than 6 weeks. Conclusion: Our results suggested that health complications were found in women who self-medicated misoprostol for induced abortions after gestational ages greater than 6 weeks during the COVID-19 lockdown.